Visceral Adiposity Index: An Effective Tool for Predicting Metabolic Syndrome in Bangladeshi Adult Population - Tabassum, Mariya; Mozaffor, Miliva; Muna, Farzana Zaman; Rahman, Md Matiur; Khan, Md Tariqul Islam; Naznen, Farhana; Chowdhury, Mehdi Ashik; Sharmin, Shegufta (Mugda Medical College Journal, 2023)
Background: Obesity induces adipocyte dysfunction with secretion of adipokines, which results in a cascade of chemical reaction which triggers the atherogenic process and insulin resistance leading to a set of metabolic abnormalities i.e., metabolic syndrome. The Visceral Adiposity Index (VAI) is a simple, gender-based obesity index and has been proposed to be a predictor of metabolic syndrome. Objective: Our study aims to evaluate the effectiveness of the Visceral Adiposity Index (VAI) in prediction metabolic syndrome in Bangladeshi adult population. Methods: This cross-sectional study was carried out in Department of Biochemistry and Molecular Biology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from January to June of 2017. A total of 200 apparently healthy subjects (108 men and 92 women) were selected for the study, who attended the out-patient-departments of the same institution. Anthropometric measurements were recorded, e.g., height, weight, waist circumference (WC). Body mass index (BMI) was calculated. Overnight fasting blood samples were collected to estimate plasma glucose and serum lipid profile. Then VAI was calculated for men and women separately and evaluated as a tool in diagnosis of metabolic syndrome among the participants. Receiver operating characteristic (ROC) curves were plotted to assess the performance of VAI in metabolic syndrome prediction by gender. The power of metabolic syndrome prediction was quantified by the area under the curve (AUC) with 95% confidence intervals. Results: The mean age of the study participants was 42.4±5.2 years. Among 108 men, 63 had metabolic syndrome, while among 92 women, 31 had metabolic syndrome. Sensitivity and specificity of VAI in predicting metabolic syndrome in male study subjects were 83.2% and 70.3%, respectively, while in female study subjects 80.1% and 70.5% respectively. Receiver operating characteristic (ROC) curve analysis showed that the optimal cutoff value of VAI in male study subjects was 2.16 and area under the curve (AUC) value was 0.907, while in female study subjects, the values were 2.25 and 0.918 respectively (P<0.001). Conclusion: The Visceral Adiposity Index (VAI) was found simple, accessible, and effective obesity index to predict metabolic syndrome in apparently healthy adults. Mugda Med Coll J. 2022; 5(2): 88-92